2014
DOI: 10.1007/978-1-4614-3209-8_31
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of the Ubiquitin-Proteasome Pathway in RPE Alters the Expression of Inflammation Related Genes

Abstract: The ubiquitin-proteasome pathway (UPP) plays an important role in regulating gene expression. Retinal pigment epithelial cells (RPE) are a major source of ocular inflammatory cytokines. In this work we determined the relationship between impairment of the UPP and expression of inflammation-related factors. The UPP could be impaired by oxidative stress or chemical inhibition. Impairment of the UPP in RPE increased the expression of several inflammatory cytokines, such as IL-6 and IL-8. However, the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 65 publications
3
19
0
Order By: Relevance
“…A previous study found that deficiency in ubiquitin ligase led to the accumulation of neurofilament light chain and to neurodegeneration 26 . Impairment of the ubiquitin-proteasome pathway can also disrupt signal transduction pathways resulting in inflammation and angiogenesis; both are important features of AMD 27 . Therefore, dysfunction of ubiquitin protein ligase (E3) may lead to the accumulation of extracellular deposits (a component of drusen), degeneration of photoreceptors and the retinal pigment epithelium (RPE), and late-stage AMD.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that deficiency in ubiquitin ligase led to the accumulation of neurofilament light chain and to neurodegeneration 26 . Impairment of the ubiquitin-proteasome pathway can also disrupt signal transduction pathways resulting in inflammation and angiogenesis; both are important features of AMD 27 . Therefore, dysfunction of ubiquitin protein ligase (E3) may lead to the accumulation of extracellular deposits (a component of drusen), degeneration of photoreceptors and the retinal pigment epithelium (RPE), and late-stage AMD.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that multiple risk factors for AMD are associated with changes in the physiological functions of RPE cells; for example, oxidants can induce apoptosis of RPE cells [ 13 ] and abnormal secretion of inflammatory factors [ 14 ]. Cigarette smoke extract can also induce apoptosis of RPE cells [ 15 ] and up-regulation of vascular endothelial growth factor (VEGF) expression [ 16 ], while a high-fat diet may result in up-regulation of interleukin-8 (IL-8) and VEGF expressions in RPE cells [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the exact function of CagA in the activation of NF-κB and the NF-κB-dependent inflammatory response have not been well characterized. Emerging evidence indicated that post-translational modification, including ubiquitination and acetylation, has important roles in various biological events, including inflammation (55)(56)(57)(58)(59)(60). Among these, the acetylation of the NF-κB p65 sub-unit has been shown to have an important role in its activation (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%